MATLAB guide for analyzing countermovement jump strategies and performance over time - Harry, J. R. (Strength and Conditioning Journal, 2021)
Valid and reliable countermovement vertical jump (CMJ) assessments using force platforms can require complex data analysis processes not typically explored during strength and conditioning professionals` training. Although commercially available software programs with focused functionality for force platform-based CMJ analyses have become accessible to help simplify the process, such programs require costly annual subscriptions and can promote reliance on the "black box" for analysis. The purpose of this report was to provide a guide and template aimed to help strength and conditioning professionals create data analysis programs using MATLAB to monitor CMJ performance and performance changes across multiple testing sessions. The guide focuses on programming strategies to import multiple CMJ trials, treat data (i.e., filtering), calculate performance and strategy variables, and create graphics documenting an athlete`s performance changes over time. The provided example script can be used as standalone analysis program for the CMJ, to help coaches learn basic script-writing strategies to create their own analysis programs for the CMJ and other performance tests, or both. Ultimately, strength and conditioning professionals should seek to have ownership of their data and analysis processes, and this guide can help coaches start or continue that process.